Engaging Entrepreneurial Etiquette : Driven by a Theory of Planned Behaviour - Pang, Kim Kwong; Shamuganathan, Gomathi (AeU, 2015)
Research Objective: The aim of this study is to analyze the entrepreneurial etiquette (EE) intention, behavior, and employer engagement with a group of Hospitality firms in Kuala Lumpur. Methodology: Based on the three elements of behavior; attitude, subjective norms and perceived behavioral control, derived from a Theory of Planned Behavior. The empirical analysis is focused on the testing of the strength of these predictors toward customer satisfaction. In addition, 376 entrepreneurs from the industry were surveyed using questionnaires. Exploratory Factor Analysis (EFA) is described as orderly simplification of interrelated measures.It is a multivariate examination on the causal effect of entrepreneurial etiquette intention to customer satisfaction. Scope of investigation/Findings: The main limitation of this research is the exposures of the respondents only to the Hospitality Industry in Kuala Lumpur. The study refers to business relational activities only. The Theory of Planned Behavior Model is applied. EFA has justified that a method of determining an appropriate, justified sample size in which the aims are estimating a population value, evaluating selected feasibility issues, assessing the adequacy of instrumentation and calculating estimates for use in planning a real study. The pre-analysis of data hygiene can be employed to avoid frustrations resulting after an EFA investigation. Data have to be screened as the factor analysis builds upon correlations. Such screening includes inspection for multivariate outliers, non-normal distributions, and linear vicariate relationships between variables. The results were positive. Thus, Confirmatory Factor Analysis on this study is suggested to proceed.